Improving The Quality and Diversification of Processed Goat's Milk-Based Products in Ainuna Farm Dairy Milk - Friska Citra Agustia; Hesti Permata sari; Umi Faza Rokhmah (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Ainuna Farm Dairy Milk (AFDM) is an integrated farm that was established in June 2021 in Pamijen Sokaraja Village, Banyumas, with the main product is goat milk. Goat milk production capacity is 10 liters per day which is marketed in a simple way around the village. Priority issues for this project include low-quality goat milk products, no nutritional value information, no halal label, and basic, not attractive packaging. Aside from that, freezers for raw materials and processed products, standard and more efficient cooking equipment for milk and dairy products, and improved packaging are still required. The goals of this project include obtaining marketable products of high quality in order to increase product competitiveness, structuring documents or financial records, and establishing online marketing networks. The methods used include: 1) counseling; 2) product diversification practices and packaging improvements; 3) business management assistance. Diversification of processed goat milk has been carried out, including making popsicles and goat milk ice cream with informative and attractive packaging (equipped with product specifications and nutrition facts) as well as halal registration. Assistance in preparing documents and financial records as well as adding online marketing networks. This project has the potential to raise the economic worth and quality of products, as well as partner earnings, resulting in more independent and wealthy partners.